2021
DOI: 10.1186/s43238-021-00034-w
|View full text |Cite
|
Sign up to set email alerts
|

The technical and the social: challenges in the conservation of earthen vernacular architecture in a changing world (Jujuy, Argentina)

Abstract: Vernacular earthen architecture presents a series of relevant conservation challenges that involve designing solutions for different kinds of alterations and degradations. Other challenges of a social nature simultaneously arise and are related, among other factors, to the participation of local communities and the actions of different institutional actors. Understanding these phenomena has generally been approached from perspectives that take technical considerations and social dynamics as separate fields. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…For example, a study of the city of Djenné, a UNESCO World Heritage Site in Mali, identified contrasting perspectives on how the city's building heritage should be managed: that of the local participants, to whom the city is an everyday place to live in, and that of (international) heritage experts, who regard it as universal heritage to be preserved (Joy 2012). Similar discrepancies in perspectives have been identified all over the world (Tomasi and Barada 2021). Interestingly, the development of new architectural forms as a result of processes of cultural change (for example, multi-generational homes, communal living experiments, or so-called 'tiny houses') has received less anthropological attention thus far.…”
Section: Architecture and Changementioning
confidence: 74%
“…For example, a study of the city of Djenné, a UNESCO World Heritage Site in Mali, identified contrasting perspectives on how the city's building heritage should be managed: that of the local participants, to whom the city is an everyday place to live in, and that of (international) heritage experts, who regard it as universal heritage to be preserved (Joy 2012). Similar discrepancies in perspectives have been identified all over the world (Tomasi and Barada 2021). Interestingly, the development of new architectural forms as a result of processes of cultural change (for example, multi-generational homes, communal living experiments, or so-called 'tiny houses') has received less anthropological attention thus far.…”
Section: Architecture and Changementioning
confidence: 74%
“…Through the understanding and absorption of these papers in the process of writing this one, the connotation of Heilongjiang traditional culture gradually emerged, and especially the degree of the influence of immigrant culture on the province. In the process of heritage protection, we should not only unilaterally pursue its essence, but also comprehensively consider the issues to achieve economic and social sustainability [20,21].…”
Section: Literature Reviewmentioning
confidence: 99%
“…While in the Church of Uquía this included the use of layers of cement mortar and plastic membranes, in the Casa del Marques during part of the 20th century, the mud cake was replaced by an integral tile roof. In both cases, the solutions not only failed to improve the performance of the roofs, but also generated diverse pathologies, particularly in Uquía (Tomasi, Barada, 2021). In this framework, the institutionalisation of the conservation of these heritages, with their associated management models, implied the incorporation of materials and techniques that are also integrated in the institutional technical valuations.…”
Section: Technical Approachesmentioning
confidence: 99%